Analytical and Numerical Study for the Determination of a Thermoelectric Generator’s Internal Resistance - Loise Rissini Kramer; Anderson Luis Oliveira Maran; Samara Silva de Souza; Oswaldo Hideo Ando Junior (Energies, 2019)
The conversion of residual thermal energy into electricity using TEGs (Thermoelectric Generators) arises as a promising technological alternative for increasing energy efficiency and power generation. In order to optimize the performance of TEGs, it is known that the maximum output power is obtained by matching the impedances between the TEG and the connected load. Therefore, the objective of this work is to present the development of a numerical and a simplified analytical model to determine the internal resistance (Rint) and predict the open circuit voltage, charge voltage, current and power values of TEGs. The models have used as reference the thermoelectric module TEHP 1263-1.5 (Thermonamic), with the analytical one being based on the classical theory of electrical circuit analysis and, for the numerical one, a three-dimensional geometric model was developed and the set of equations were solved in the COMSOL Multiphysics® tool by the finite element method. The Rint obtained by the analytical and numerical models were, respectively, 3.157 Ω and 6.027 Ω, and the value supplied by the supplier is 3.154 Ω. Therefore, the analytical model is indicated as a reference to estimate Rint of the TEG, allowing optimizing its use by choosing the load resistance that will result in the maximum power.